E-waste management at recovery facilities in Klang Valley / Nurul Ain Mohd Nordin - Nurul Ain , Mohd Nordin (2017)
‘E-waste’ which is the term used to describe electrical and electronic waste, have been rising sharply in its generation. This is due to increased use of electrical and electronic equipments. The implication of this increase in e-waste and its improper disposal will lead to major problems to human health and environment. E-waste recycling is a very important industry to recover valuable components in e-waste which can contribute to significant economic value, and to reduce pollution caused by improper disposal of e-waste that contain hazardous materials. Material recovery facility (MRF) is an important element in e-waste recycling. Through MRF, valuable parts of e-waste are processed and recovered. The objective of this study is to analyze the flow of e-waste among MRF using material flow analysis (MFA) model. MFA modeling would include collection, sorting, recovery and disposal. Furthermore, MFA also led to better system analysis which aid in giving practical recommendations for sustainable management of e-waste in MRF. 15 MRF in Klang Valley participated in this study. Five of them are full recovery facilities and the other 10 are partial recovery facilities. Data were collected by using questionnaires / survey and interview with the relevant stakeholders. Observation during site visit was done to explore e-waste management at these recovery facilities. STAN (subSTance flow ANalysis) 2.5 software was used to perform the MFA modeling. The findings showed that MRF of e-waste in Malaysia needs to comply with legal requirements set by the government to avoid improper management of hazardous waste. Environmental Management System (EMS) is also one of the criteria practised by hazardous waste management facility in Malaysia. All of recovery facilities involved in this study are licensed by Department of Environment, Malaysia and followed the stipulated regulations. The constructed MFA model showed that these recovery facilities collected approximately 263 tonnes of e-waste per month. Personal computers and laptops were the highest e-waste collected (42%). Crushing is the most popular method used by the recovery facilities involved. The products are sold as recyclables, 200,000 kg/month (90%), sent to other recovery facilities for further recovery, 2,800 kg/month (2%), or exported to other countries, 19,000 kg/month (8%). The hazardous residues and non-hazardous wastes generated are disposed at Kualiti Alam and municipal solid waste landfill at 20,000 kg/month (60%) and 14,500 kg/month (40%), respectively. This research helps us to understand various ongoing activities within MRF and thus, encourage the formulation for a proper e-waste management strategy in Malaysia.